2021
DOI: 10.1177/09576509211046998
|View full text |Cite
|
Sign up to set email alerts
|

Cavitation in a high-speed aviation axial piston pump over a wide range of fluid temperatures

Abstract: The axial piston pump in aerospace applications needs to operate over a wide range of fluid temperatures from −54°C to 135 °C. The fluid properties at such extreme temperatures will significantly affect the cavitation that is one of the major limiting factors for the efficiency and reliability of aviation axial piston pumps. However, it appears that very little of the existing literature studies the effects of extreme fluid temperatures on the pump cavitation. This paper aims to examine the temperature effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The visual observation of cavitation was impossible for the test pump due to its nontransparent metallic pump housing. The volumetric loss ratio was adopted to indicate the cavitation conditions since more serious cavitation led to higher volumetric losses [8, 9]. The accelerometer collected vibration data with a sampling frequency of 10,240 Hz.…”
Section: Experimental Investigationmentioning
confidence: 99%
See 1 more Smart Citation
“…The visual observation of cavitation was impossible for the test pump due to its nontransparent metallic pump housing. The volumetric loss ratio was adopted to indicate the cavitation conditions since more serious cavitation led to higher volumetric losses [8, 9]. The accelerometer collected vibration data with a sampling frequency of 10,240 Hz.…”
Section: Experimental Investigationmentioning
confidence: 99%
“…The increasing demand on great power to weight ratio has stimulated the development of high‐speed axial piston pumps [4, 5], particularly in aerospace applications [6, 7]. However, cavitation is likely to occur in axial piston pumps operating at high rotational speed [8], which leads to volumetric loss [9], vibration noise [10], and cavitation erosion [11]. More seriously, the cavitation may even result in pump failure and threaten the safety of the entire hydraulic system.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the ratio of vaporization of the working fluid to convective heat transfer increased with increases in the inlet liquid temperature. Chao Qun et al [19] studied the effect of temperature on cavitation in axial piston pumps and found that low-temperature fluid produces severe cavitation phenomena due to the high viscosity, and high-temperature fluid has less effect on cavitation. Peralta et al [20] proposed a non-bearing pump capable of conveying 250 • C fluid, studied its internal working temperature, and verified its thermal and hydraulic performance through tests.…”
Section: Introductionmentioning
confidence: 99%
“…The usual and most effective way of avoiding incomplete filling consists of boosting the pump, but such a solution is not always feasible or economically convenient. All these problems are well known in the aeronautical field, where the increment in the power-to-weight ratio requires the use of small displacement pumps, typically axial-piston type, but with extreme operating speeds [26].…”
Section: Introductionmentioning
confidence: 99%